Anopheles Mosquito Species in Betung Bedarah, Tebo Regency, Jambi Province - Maloha, Maas M; Ratnaningrum, Kanti (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2021)
Background: Indonesia is a tropical country which is a good breeding ground for mosquitoes. Mosquitoes are still one of arthropods that contribute to occurrence of infectious diseases, including malaria, which is a disease that is a health problem in Jambi Province.Objective: To determine types of Anopheles mosquito spesies in Betung Bedarah Tebo, Jambi.Methods: A discriptif study to identifed distribution of mosquitoes in Betung Bedarah, Tebo Regency used human landing collection and resting collection methods. Collection of mosquito samples used an aspirator and light trap. Analysis used tabulation.Results: Of the 64 mosquitoes collected, 25% were Anopheles mosquitoes which consisted of 43.7% Anopheles barbirostris, 25% Anopheles vagus, 18.7% Anopheles aconitus, and 12.6% Anopheles kochi.Conclusion: Most of mosquito species collected at Betung Berdarah Tebo were Anopheles barbirostris.